Prodrugs of imidazotriazine and pyrrolotriazine C-nucleosides can increase anti-HCV activity and enhance nucleotide triphosphate concentrations in vitro. Issue 4 (15th February 2015) - Tyndall, Edward M.; Draffan, Alistair G.; Frey, Barbara; Pool, Brett; Halim, Rosliana; Jahangiri, Saba; Bond, Silas; Wirth, Veronika; Luttick, Angela; Tilmanis, Danielle; Thomas, Jesse; Porter, Kate; et al.
Graphical abstract